Functional outcomes after treatments for different types of isolated ulnar coronoid fracture: A protocol for systematic review. Issue 19 (May 2020) - Chen, Hongwei; Wu, Jinqing; Zhao, Pinyi; Wu, Lijun; Guo, Chao
Abstract: Background: Optimal treatments for ulnar coronoid fracture have yet to be determined. We aimed to systematically review treatment efficacy assessed by functional outcomes of patients with isolated ulnar coronoid fracture. Methods: Medline, Cochrane Library, EMBASE, and Google Scholar were searched for studies reporting quantitative outcomes data after surgical treatment for isolated ulnar coronoid fractures up to July 16, 2019. Functional outcomes determined using disabilities of the arm, shoulder and hand score; Mayo elbow performance score (MEPS); and range of motion were systematically reviewed. Results: Six studies with a total of 65 patients with isolated coronoid fracture who had received surgical treatment were included. All studies were of good quality according to a modified Delphi checklist. Most patients had Type II fractures based on Regan-Morrey or O'Driscoll classification. Disabilities of the arm, shoulder and hand scores were reported by 2 studies (mean range 5–17). Four studies reported MEPS (mean range 89–98). One study reported Broberg-Morrey scores, in which 93% patients achieved excellent or good outcomes. Five studies reported range of motion, with mean flexion ranging from 122 to 137 and mean extension ranging from 4.0 to 21 degrees. Quantitative analyses revealed that lateral, medial, or posterior approaches in treating Type II fractures are associated with higher postoperative MEPS and flexion scores than the anteromedial approach. Conclusions: Treatment efficacy assessed by functional outcomes for isolated ulnar coronoid fractures is overall satisfactory. Whether lateral, medial, or posterior approaches lead to more favorable outcomes than the anteromedial approach is inconclusive. Further prospective studies are warranted.